Saberes históricos interdisciplinares: história e ensino da pesquisa para formação de pesquisadores no bairro do Anjo da Guarda - PEREIRA, Welton Vale (2024)
This analysis focuses on the routines of teachers and students at a school in the Anjo da Guarda neighborhood, located in the Itaqui-Bacanga region of São Luís, Maranhão. It is based on the concept of interdisciplinarity as presented by Fazenda (1993), Freire (1996), and Santos (2019), with the aim of developing a historical consciousness as defined by Rüsen (2001), which is understood as a form of human consciousness directly related to practical human life. The study employs a qualitative descriptive analysis methodology anchored in an intervention project at the research school. This approach allows for breaking the boundaries of the school by participating in the Interdisciplinary Research Incentive Seminar – SEMIP, where the experiences and experiments developed by teachers and students from the school are shared. Data for this pedagogical extension exercise is collected through observation, interviews, and questionnaires applied to the target audience to quantify the initially intended results. The findings prompted the suggestion, through a Pedagogical Notebook, which complements this master's dissertation, to offer basic guidelines so that individuals in other educational contexts may replicate these experiences and experiments. It is assumed that this methodology could be of immeasurable value for improving teaching and learning outcomes for students in the final years of elementary education at the research school.